2015
DOI: 10.1158/0008-5472.can-14-2277
|View full text |Cite
|
Sign up to set email alerts
|

Akt Inhibition Enhances Expansion of Potent Tumor-Specific Lymphocytes with Memory Cell Characteristics

Abstract: Adoptive cell therapy (ACT) using autologous tumor-infiltrating lymphocytes (TIL) can result in complete regression of advanced cancer in some patients, but the efficacy of this potentially curative therapy might be limited by poor persistence of TIL after adoptive-transfer. Pharmacologic inhibition of the serine/threonine kinase Akt has recently been shown to promote immunologic memory in viral-specific murine models, but whether this approach may enhance features of memory (e.g. long-term persistence) in TIL… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
254
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 308 publications
(275 citation statements)
references
References 40 publications
19
254
0
2
Order By: Relevance
“…Confirming previously published data, 15,16,18 AKT-inhibited T cells showed increased secondary expansion capacity after removal of the inhibitor. Moreover, we found that next to IFN-γ, AktiVIII and GDC-treated T cells also produced IL-2, which was not observed in control T cells.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Confirming previously published data, 15,16,18 AKT-inhibited T cells showed increased secondary expansion capacity after removal of the inhibitor. Moreover, we found that next to IFN-γ, AktiVIII and GDC-treated T cells also produced IL-2, which was not observed in control T cells.…”
Section: Discussionsupporting
confidence: 90%
“…This uncoupling of T cell differentiation from expansion using AKT-inhibitors has been confirmed in other models, including melanoma-derived tumor-infiltrating lymphocytes and CD19 CAR T cells, as well as by modulation of up- and down-stream targets of the AKT-pathway, including mTORC2 and PI3K-δ. 16-18,20,21 …”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies have revealed that this might not be the case. Akt inhibition has been employed in preclinical and translational settings as a means to reinvigorate TIL expansion, in part through modulating oxidative metabolism (Crompton et al, 2015). In addition, T cells lacking the mammalian target of rapamycin complex 2, the kinase for the hydrophobic motif (serine 473, measured in this study) of Akt, show superior effector function and increased oxidative metabolism, suggesting full Akt activation might not be acutely required for effector function (Pollizzi et al, 2015).…”
Section: Discussionmentioning
confidence: 87%
“…Thus, pharmacological inhibition of PKB in cancers not only significantly dampens PKB mediated cancer cell proliferation and metabolic adaption, but also enable an effective immune editing program by favoring the re-activation of immune cells via down-regulating inhibitory signals. Indeed, in a mouse transplantation model, inhibition of PKB with an allosteric inhibitor (PKB inhibitor VIII) reprograms the tumor-infiltrated CD8 + T cells into phenotypic memory cell types coupled with an enhanced and prolonged anti-tumor effect [89]. A similar effect was confirmed with a grafted myeloma mouse model [90].…”
Section: Targeting Pkb In Tumor-associated Inflammationmentioning
confidence: 90%